Connection between competence, usability, environment and risk of falls in elderly adults - José Alex Leiva-Caro; Bertha Cecilia Salazar-González; Esther Carlota Gallegos-Cabriales; Marco Vinicio Gómez-Meza; Kathleen F. Hunter (Universidade de São Paulo, 2015)
Objective: to determine connections between competence, usability, environment and risk of falls in elderly adults. Method: correlational descriptive study, 123 elderly adults, both male and female, aged 70 years and older were included. Data was collected via the Tinetti Scale, CESD-7 Scale, Montreal Cognitive Assessment, Usability Questionnaire on Housing and Housing Enabler; and sociodemographic and health background certificate data. For data analysis, descriptive and inferential statistics were used, multivariate linear and logistic regression models were adjusted. Results: 42.0% of the elderly adults had presented with falls, with a higher prevalence in women, and in the group of 70-75 years. The physical environment of the house, gait, and usability were set as risk factors for falls. A negative relationship between usability and depressive symptoms, cognitive health, balance, gait, the social and physical environment was found, p <0.05; and a strong positive correlation between walking and balance, p <0.05. Conclusion: this study helps to better understand the phenomenon of falling, to find a connection between usability with the risk of falls, and other variables.